The one‐year impact of accountable care networks among Washington State employees. (16th April 2021) - Coe, Norma B.; Ingraham, Bailey; Albertson, Elaine; Zhou, Lingmei; Wood, Suzanne; Grembowski, David; Conrad, Douglas
Abstract: Objective: To estimate the impact of a new, two‐sided risk model accountable care network (ACN) on Washington State employees and their families. Data Sources/Study Setting: Administrative data (January 2013‐December 2016) on Washington State employees. Study Design: We compared monthly health care utilization, health care intensity as measured through proxy pricing, and annual HEDIS quality metrics between the five intervention counties to 13 comparison counties, analyzed separately by age categories (ages 0‐5, 6‐18, 19‐26, 18‐64). Data Collection/Extraction Methods: We used difference‐in‐difference methods and generalized estimating equations to estimate the effects after 1 year of implementation for adults and children. Principal Findings: We estimate a 1‐2 percentage point decrease in outpatient hospital visits due to the introduction of ACNs (adults: −1.8, P < .01; age 0‐5: −1.2, P = .07; age 6‐18: −1.2, P = .06; age 19‐26; −1.2, P < .01). We find changes in primary and specialty care office visits; the direction of impact varies by age. Dependents age 19‐26 were also responsive with inpatient admissions declines (−0.08 percentage points, P = .02). Despite changes in utilization, there was no evidence of changes in intensity of care and mixed results in the quality measures. Conclusions: Washington's state employee ACN introduction changed health care utilization patterns in the first year but was not as successful in improving quality.